Implications of game theory for theoretical underpinning of cooperative relations in workplace partnership. Issue 3 (19th May 2013) - Trif, Aurora; Brady, Malcolm
Abstract This article clarifies the ongoing debate over the key factors underpinning cooperative relations between management and trade unions by drawing on the once‐off and repeated prisoner's dilemma models. It argues that the lower the risk to achieve a 'win‐win' outcome and the longer the time horizon for workplace partnership, the more likely is for the two parties to cooperate.